Exploring Teachers Understanding And Problems In Class Action Research And Writing Articles In Journals - Umar Kalmar Nizar; Guspatni Guspatni; Fauzana Gazali (Fakultas MIPA Universitas Negeri Padang, 2020)
Writing scientific papers is very important for today's teachers and it is also an obligation for current teachers to be promoted. However, many teachers experience problems in doing so, such as not understanding how to write it, how to start and the time available. To be able to write KTI, the teacher must have data. This data can be obtained by the teacher through classroom action research. .